Professoras negras no Ensino Superior no Amazonas: um olhar interseccional - Nascimento, Júlia do (2023)
This dissertation is the result of research carried out in two public institutions of higher education, the State University of Amazonas (UEA) and the Federal University of Amazonas (UFAM), by the Interdisciplinary Graduate Program in Human Sciences (PPGICH/ UEA), for the Master's degree, which analyzed the challenges of black female university professors through an intersectional perspective. For that, the methodology applied was the "snowball sampling" method, where through questions asked to students of different graduations of UEA and UFAM in their social networks, it was discovered whether there was the presence of black women as teachers in their courses or not. The interviewed participants were self-declared black women aged between 33 and 55 who worked as professors at UEA or UFAM in the period between September and December 2022. The interviews were carried out in person and online according to the availability of the interlocutors, where their speeches were recorded from a semi-structured script to answer the main question: What are the challenges of a black woman university professor? Thus, the established objectives of identifying the main challenges of professional practice and how these teachers deal with these challenges were achieved. I reiterate my satisfaction in completing this research, pointing out that the interlocutors who took part in this research are multiple and respond to the challenges that are imposed by the profession with unique and complex views that lead to reflection on the challenges that society demands and how these challenges can be faced.